1990
DOI: 10.1017/s0022112090001689
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent boundary layer relaxation from convex curvature

Abstract: A study was undertaken to examine the flat plate relaxation behaviour of a turbulent boundary layer recovering from 90° of strong convex curvature (δ0/R = 0.08), for a length of ≈ 90δ0 after the end of curvature, where δ0 is the boundary layer thickness at the start of the curvature. The results show that the relaxation behaviour of the mean flow and the turbulence are quite different. The mean velocity profile and skin friction coefficient asymptotically approach the unperturbed state and at the last measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 7 publications
8
28
1
Order By: Relevance
“…The behaviour of the shear stress and normal stress ratio in the present flow is quite different than that measured in previous experiments on boundary layers experiencing extended convex curvature (in the absence of an external pressure gradient), in which the shear stress is strongly reduced and the normal stresses approach isotropy (e.g. see So & Mellor 1973;Gillis & Johnston 1983;Alving et al 1990). Thus, it should be expected that the relaxation process will be different than the slow recovery observed in boundary layers recovering from convex curvature (see also Webster et al 1996).…”
Section: Turbulence Statisticscontrasting
confidence: 94%
See 2 more Smart Citations
“…The behaviour of the shear stress and normal stress ratio in the present flow is quite different than that measured in previous experiments on boundary layers experiencing extended convex curvature (in the absence of an external pressure gradient), in which the shear stress is strongly reduced and the normal stresses approach isotropy (e.g. see So & Mellor 1973;Gillis & Johnston 1983;Alving et al 1990). Thus, it should be expected that the relaxation process will be different than the slow recovery observed in boundary layers recovering from convex curvature (see also Webster et al 1996).…”
Section: Turbulence Statisticscontrasting
confidence: 94%
“…For example, in a related study by Alving et al (1990), although the criterion established by Baskaran et al (1987) for generation of an internal layer due to curvature change was satisfied in their experiments, signatures of an internal layer could not be found. Alving et al (1990) suggested that the concept of an internal layer growing from the wall with its origin at the curvature discontinuity and remaining uninfluenced by the flow in the parent boundary layer for significant distances, might be too simplistic (see Patel & Sotiropoulos 1997 for further discussion). On the other hand, recent measurements by Webster et al (1996) clearly show distinct 'knees' in profiles of the streamwise intensity downstream of the bump trailing edge and imply the generation of an internal layer.…”
Section: Objectivesmentioning
confidence: 90%
See 1 more Smart Citation
“…(c) (d) Figure 4: Effect of spatial resolution on boundary layer profiles at x 1 /δ 0 = 100. Experimental data of Elena and Lacharme [79], Alving [78], and Konrad [80], and computational data of Pirozzoli and Bernardini [48] are shown for comparison. …”
Section: Discussionmentioning
confidence: 99%
“…Moin and Kim 6 and Kim and Moin 7 performed correlation studies on vorticity fields in channel flows and concluded that the most probable inclination angle of a vortex is 45 ‫ؠ‬ to the streamwise direction. Experimental studies of structure angle using two-point correlation measurements 8 have found that the "inferred" angle is seldom equal to 45 ‫ؠ‬ . Marusic 9 performed attached eddy calculations and showed that such a result is consistent with the presence of individual eddies inclined at 45 ‫ؠ‬ , given that, however, these 45 ‫ؠ‬ eddies exist over a range of length scales and population densities.…”
Section: Introductionmentioning
confidence: 99%